Antimicrobial Activity of Extracts of Daniella oliveri Stem Bark on Selected Clinical Isolates - Brown, Samuel Tamunoiyowuna Cockeye; Mohammed, Ikrimah Usman; Adam, Habiba Idris (Darul Yasin Al Sys, 2024)
The utilization of medicinal plants in therapy has gained popularity due to increased trust in herbal medicine, attributed to properties such as antioxidant, antimicrobial, and antipyretic effects conferred by phytochemicals present in them. This study aimed to evaluate the antibacterial activity of Daniella oliveri stem bark against clinical isolates. The sample was air dry at room temperature for 7 days. Exactly 400 g of the air dried samples was weighed and soaked in 1000 mL each of ethanol and water respectively for 72 hours and were extracted using decoction method. The ethanol and aqueous extracts of the bark of the Daniella oliveri was tested against Staphylococcus aureus, Bacillus spp., Klebsiella pneumonia and Planococcus glaciei isolates. The ethanol extract of the bark was inhibitory against Staphylococcus aureus, Bacillus spp. and Klebsiella pneumonia with the highest zone of inhibition of 14±0.00 mm, 17±10.6 mm and 25±10.5 respectively, while the aqueous extracts of bark was active against Staphylococcus aureus, Bacillus spp. and Klebsiella pneumonia with zone of inhibition of 14±0.00 mm, 13±10.4 mm and 25±0.00 respectively. MICs ranged from 50 mg/mL to 25 mg/mL for ethanol and 100 mg/mL to 25 mg/mL for aqueous extracts, with no activity observed at 200 mg/mL. MBC results were observed at 100 mg/mL and 200 mg/mL for ethanol and aqueous extracts respectively. The study concluded that Daniella oliveri possesses significant antibacterial activities, supporting its traditional use. Further research is warranted to purify and utilize the active inhibitory substance as an alternative treatment for infections associated with the test organisms.